2020
DOI: 10.3390/plants9020134
|View full text |Cite
|
Sign up to set email alerts
|

Macrophomina Crown and Root Rot of Pistachio in California

Abstract: In this study, declining pistachio rootstocks were detected in newly planted commercial pistachio orchards in Kern County, California. Symptoms were characterized by wilted foliage combined with crown rot in the rootstock. From diseased trees, 42 isolates were obtained, and all had similar cultural and morphological characteristics of Macrophomina phaseolina. Analyses of nucleotide sequences of three gene fragments, the internal transcribed spacer region (ITS1–5.8S–ITS2), partial sequences of β-tubulin, and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…This pathogen causes charcoal rot of soybean (Sarr et al, 2014), chickpea (Dell'Olmo et al, 2022, sunflower (Bokor, 2007), sorghum (Sharma et al, 2014), and strawberry (Koike, 2008). It has also been reported to cause diseases on woody hosts, such as grapevine (González and Tello, 2011;Nouri et al, 2018), olive (Sergeeva et al, 2005), pistachio (Nouri et al, 2020), and almond (Inderbitzin et al, 2010). Macrophomina phaseolina was thought to be one of the pathogens causing avocado root rot in Australia (Poudel et al, 2021), but it has not been recorded as causing canker on this host.…”
Section: Discussionmentioning
confidence: 99%
“…This pathogen causes charcoal rot of soybean (Sarr et al, 2014), chickpea (Dell'Olmo et al, 2022, sunflower (Bokor, 2007), sorghum (Sharma et al, 2014), and strawberry (Koike, 2008). It has also been reported to cause diseases on woody hosts, such as grapevine (González and Tello, 2011;Nouri et al, 2018), olive (Sergeeva et al, 2005), pistachio (Nouri et al, 2020), and almond (Inderbitzin et al, 2010). Macrophomina phaseolina was thought to be one of the pathogens causing avocado root rot in Australia (Poudel et al, 2021), but it has not been recorded as causing canker on this host.…”
Section: Discussionmentioning
confidence: 99%
“…M. phaseolina also poses a great threat to specialty crops, such as strawberry, pistachio, and sunflower ( Mertely et al., 2005 ; Bokor, 2007 ; de los Santos et al., 2019 ; Nouri et al., 2020 ). Research on specialty crops is often underfunded and disproportionately lacking in comparison to the steady rise in value of production, despite the inherently high risk involved in marketing fresh produce ( Alston and Pardey, 2008 ; Neill and Morgan, 2021 ).…”
Section: Phaseolina : a Global “Crop Destroyer”mentioning
confidence: 99%
“…However, as this problem proved to be non-transmissible in the field, and nurseries can now identify it in young rootstocks, it is no longer a problem. Nouri et al [238] reported a new pathogen, Macrophomina phaseolina in Kern County of California which is characterized by wilted foliage combined with crown rot of the rootstock. UCB1 is highly susceptible to M. phaseolina and this pathogen is now an emerging threat to pistachio production in California.…”
Section: Resistance To Biotic Stressesmentioning
confidence: 99%